2019
DOI: 10.1074/jbc.ra119.009065
|View full text |Cite
|
Sign up to set email alerts
|

S-Acylation controls functional coupling of BK channel pore-forming α-subunits and β1-subunits

Abstract: The properties and physiological function of pore-forming α-subunits of large conductance calcium- and voltage-activated potassium (BK) channels are potently modified by their functional coupling with regulatory subunits in many tissues. However, mechanisms that might control functional coupling are very poorly understood. Here we show that S -acylation, a dynamic post-translational lipid modification of proteins, of the intracellular S0–S1 loop of the BK channel pore-forming α-subunit c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…S-acylation of the S0–S1 site by zDHHC23 is required for efficient forward trafficking of the pore-forming subunit alone to the plasma membrane. Indeed, genetic knockdown of zDHHC23, or site-directed mutagenesis of Cys53 : 56 to alanine results in reduced cell surface expression and enhanced retention of the α-subunit in the endoplasmic reticulum [ 53 55 ]. The S0–S1 site is de-acylated by the thioesterases APT1 (Lypla1) and the related APT1-like thioesterase (Lyplal1) resulting in enhanced retention in the trans Golgi network [ 55 , 56 ].…”
Section: Insulin Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…S-acylation of the S0–S1 site by zDHHC23 is required for efficient forward trafficking of the pore-forming subunit alone to the plasma membrane. Indeed, genetic knockdown of zDHHC23, or site-directed mutagenesis of Cys53 : 56 to alanine results in reduced cell surface expression and enhanced retention of the α-subunit in the endoplasmic reticulum [ 53 55 ]. The S0–S1 site is de-acylated by the thioesterases APT1 (Lypla1) and the related APT1-like thioesterase (Lyplal1) resulting in enhanced retention in the trans Golgi network [ 55 , 56 ].…”
Section: Insulin Secretionmentioning
confidence: 99%
“…For example, assembly of the α-subunit with the β1-subunit, that is highly expressed in vascular smooth muscle cells, overrides the deficit in cell surface delivery of the de-acylated α-subunit but reduces the functional coupling between α- and β1-subunit. Thus, while BK channels are efficiently delivered to the cell surface, their activity is reduced as the normal effect of the β1-subunit to shift the voltage for half-maximal activity into the more physiological range of negative potentials is attenuated when the S0–S1 loop is de-acylated [ 53 ]. In addition, the regulatory β4 subunit that is expressed in many endocrine tissue including the pancreas is itself S-acylated and the S-acylated β4-subunit can enhance cell surface expression of a-subunits by facilitating ER exit [ 60 ].…”
Section: Insulin Secretionmentioning
confidence: 99%
“…The generation of BK channel ZERO and STREX variant subunits with an extracellular N-terminal FLAG-and intracellular C-terminal -HA epitope by guest on November 4, 2020 http://www.jbc.org/ Downloaded from 7 tags in pcDNA3, together with S-acylation deficient site directed mutants and the STREX-CRD domain as a -YFP fusion have been described previously (15)(16)(17). Original ABHD family clones as Flag-tagged constructs in the pCAGGS vector were a generous gift of Professor Masaki Fukata (21) and used in the initial imaging screens in Figure1.…”
Section: Bk Channel and Acyl Thioesterase Constructsmentioning
confidence: 99%
“…We have previously revealed that the trafficking, function and regulation of pore forming subunit (Kcnma1) of the large conductance calcium-and voltage activated potassium (BK) channel is controlled by S-acylation of two distinct domains ( Figure 1A). The intracellular loop between transmembrane domains S0 and S1 (S0-S1 loop) is S-acylated at a cluster of conserved cysteine residues that controls trafficking to the plasma membrane and functional assembly with regulatory b1-accessory subunits (15,16). This domain is largely S-acylated by zDHHC23 that promotes membrane trafficking of the a-subunit alone and is a target for deacylation by Lypla1 resulting in channel retention in the trans Golgi network (15).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the intracellular Ca 2+ sensors may be also coupled to E13 and T14 in the β1 N terminus to change the apparent voltage dependence with Ca 2+ present (18). Functional coupling between β1 and pore-forming Slo1 subunits also depends on S -acylation of select Cys residues within Slo1 (19).…”
Section: Introductionmentioning
confidence: 99%